Feasibility studies of polyaniline nanostructures coated on tapered optical fiber for ammonia sensing - Ibrahim @ Ghazali, Siti Azlida (2017)
Polyaniline (PANI) has been used for ammonia (NH3) sensing for several decades, mostly in electrical based sensors due to its variation in conductivity during the interaction. Optical sensors are known to have advantages in certain aspects as compared to electrical sensors, but this area of research has not been fully explored. Therefore, this research project aims to explore optical based NH3 sensor with the incorporation of PANI nanostructure. Tapered multimode fiber (MMF) was chosen as the transducing platform for the sensor because of ease in fabrication, high sensitivity and its suitability for remote sensing applications. The sensitivity of tapered fiber based sensors can be improved by reducing the waist diameter. The influence of PANI nanostructure morphology, thickness and dopants on the sensing performance was also studied in this thesis. In this project, PANI nanostructures were synthesized and deposited on tapered MMF using two methods. The first method was in-situ deposition method, where poly(methyl vinyl ether-alt-maleic acid)(PMVEA)-doped PANI (PANI-PMVEA) nanogranules and nanofibers were grown on tapered MMF surface during polymerization process. For the second method, camphorsulfonic acid (CSA)-doped PANI (PANI-CSA) nanofibers were spray coated on the tapered MMF. Three processes were involved in the preparation of PANI-CSA, namely the synthesis of hydrochloric acid-doped PANI (PANI-HCl), the dedoping of PANI-HCl to obtain emeraldine base PANI (PANI-EB) powder and the redoping of PANI-EB with CSA to obtain PANI-CSA nanostructures. The thickness and morphology of PANI nanostructures were characterized using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The formation of PANI nanostructures in emeraldine salt form was confirmed from molecular vibrational analysis using Raman Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR). The response of the sensors towards NH3 at different concentration was measured using cumulative absorbance change within the wavelength range of 500 – 800 nm. The sensing performance was evaluated in terms of response time, recovery time, sensitivity and repeatability. PANI-PMVEA coating thickness and morphology was varied by varying the deposition duration and PMVEA/aniline ratio. The highest sensitivity was achieved by the most uniformly-distributed nanogranules PANI-PMVEA coating with thickness of approximately 913 nm. The achieved sensitivity, response and recovery time was 2.19/vol%, 2.82 minutes and 11.52 minutes, respectively. PANI-CSA nanofibers were coated on tapered MMF with different waist diameters. The highest sensitivity of 2.44/vol% was attained by the smallest diameter (20 μm) sensor with PANI-CSA coating of approximately 700 – 850 nm. The response and recovery time are 1.73 minutes and 12 minutes, respectively. The sensor using PANI-CSA nanofibers have higher sensitivity and faster response than the sensor using PANI-PMVEA nanostructures at 1% NH3.